2021
DOI: 10.1002/alz.12396
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial variants and haplogroups identified by whole exome sequencing with Alzheimer's disease

Abstract: Introduction Findings regarding the association between mitochondrial DNA (mtDNA) variants and Alzheimer's disease (AD) are inconsistent. Methods We developed a pipeline for accurate assembly and variant calling in mitochondrial genomes embedded within whole exome sequences (WES) from 10,831 participants from the Alzheimer's Disease Sequencing Project (ADSP). Association of AD risk was evaluated with each mtDNA variant and variants located in 1158 nuclear genes related to mitochondrial function using the SCORE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Due to the strict maternal inheritance and negligible intermolecular recombination of mtDNA, the sequential accumulation of mtDNA mutations during prehistoric human migrations has resulted in sets of specifically linked mtDNA polymorphisms in geographically defined haplotype groups or haplogroups (mtHgs) [23] (Figure 1). Genetic variation in the mitochondrial genome, either mtHg's or individual SNPs, have been associated with ADincluding mtHg J with increased risk of AD [24][25][26]. However, there are few definitive findings across the literature, which is characterized by contradictory findings and a lack of replication due to small sample sizes, insufficient mtDNA data, and technical challenges in data analysis [24].…”
Section: Study Design and Main Resultsmentioning
confidence: 99%
“…Due to the strict maternal inheritance and negligible intermolecular recombination of mtDNA, the sequential accumulation of mtDNA mutations during prehistoric human migrations has resulted in sets of specifically linked mtDNA polymorphisms in geographically defined haplotype groups or haplogroups (mtHgs) [23] (Figure 1). Genetic variation in the mitochondrial genome, either mtHg's or individual SNPs, have been associated with ADincluding mtHg J with increased risk of AD [24][25][26]. However, there are few definitive findings across the literature, which is characterized by contradictory findings and a lack of replication due to small sample sizes, insufficient mtDNA data, and technical challenges in data analysis [24].…”
Section: Study Design and Main Resultsmentioning
confidence: 99%
“…9 All participants were sequenced through WGS to identify the GSN mutational spectrum, and meanwhile, other dementia-related gene causative mutations were excluded. The GSN mutations were further validated in two validation cohorts of the Cognitive Impairment Multicenter Database and Collaborative Network in China (CI-MDCNC), as well as the Alzheimer's Disease Sequencing Project (ADSP) [10][11][12] (online supplemental methods). The CI-MDCNC includes 884 patients with probable AD who underwent gene-targeted sequencing (online supplemental methods).…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…Besides, the GSN mutations were further validated in two cohorts from CI-MDCNC and ADSP, respectively. [10][11][12] Interestingly, three frameshift mutations (P3fs, G470fs and S552fs) were identified in the CI-MDCNC cohort, and the frequency in patients with AD (1.47%, 13/884) was higher than that of controls (0/1403, p<0.001; online supplemental table S1). However, the GSN rare frameshift mutations were not observed in the ADSP cohort, indicating that the GSN frameshift mutations might be enriched in the Chinese populations.…”
Section: Frameshift Mutations Of the Gsn Gene May Lead To Ad Gsn Gene...mentioning
confidence: 98%
“…A comprehensive in-depth analysis of more than 1000 human brain mtDNA sequence variants and abundances further confirmed the association between mtDNA deletion and AD [ 38 ]. For instance, a near-study-wide significant result was observed in AD patients with a deleterious MT-ND4L Asp88Glu missense mutation [ 28 ]. The mitochondrial-wide association study (MiWAS) also identified a mitochondrial single nucleotide polymorphism (SNP) rs2853499 that is associated with AD [ 39 ].…”
Section: Mtdnamentioning
confidence: 99%